2023
DOI: 10.1002/joe.22207
|View full text |Cite
|
Sign up to set email alerts
|

Online teaching effectiveness: Lessons from Indian universities during the Covid‐19 pandemic

Abstract: This research aims to study the effectiveness of online teaching, from student and faculty perspectives, during the Covid‐19 Pandemic in higher education institutions across India. Using the Student's Evaluation of Online Teaching Effectiveness (SEOTE) scale, a survey was conducted among 1042 students in different Indian universities. The scale measured student faculty contact (SFC), cooperation among students (CAS), active learning (AL), prompt feedback (PF), time on task (TT), high expectations (HE), and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The survival of the higher education system depends on its adaptability, resilience and sustainability [39]. The COVID-19 pandemic was both an opportunity and challenge for university education, as previously discussed by several authors [40][41][42][43][44]. Although online education provided multiple benefits for both students and teachers, including better time management and flexibility, the sudden shift to emergency online education caused a deterioration in communication skills [45].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
“…The survival of the higher education system depends on its adaptability, resilience and sustainability [39]. The COVID-19 pandemic was both an opportunity and challenge for university education, as previously discussed by several authors [40][41][42][43][44]. Although online education provided multiple benefits for both students and teachers, including better time management and flexibility, the sudden shift to emergency online education caused a deterioration in communication skills [45].…”
Section: Discussion and Concluding Remarksmentioning
confidence: 97%
“…As Mahajan et al. (2023) documented that lack of training resources and infrastructure were major problems faced by HEIs during the global pandemic. Talent management and talent development may help resolving the problems inflicted by global pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In HEIs, faculty need to exhibit talent engagement in the delivery of lectures and in conducting research. A recent study conducted on HEIs in India, survey from 1042 students and 60 faculty members revealed that lack of training resources and infrastructure were major problems faced during the global pandemic (Mahajan et al., 2023). To overcome these difficulties, it is necessary for the faculty to exhibit higher levels of talent engagement.…”
Section: Theory Literature Review and Hypothesesmentioning
confidence: 99%
“…This abrupt shift to online education, initially created various arguments including 'digital challengers' [263,265], 'continuing education further' [242,264,[266][267][268] and 'remodel in the midst of a crisis' [269]. As the online approach became widespread in the middle of 2020, it was critiqued for a number of reasons, including students' ability to focus, interest, motivation, quality, access, interactions, digital connectivity, and support system [28,[270][271][272][273][274][275][276][277][278][279] and many more. These were concerns for ECs, as EE was generally delivered through a integration of lectures, tutorials, laboratory practical, team work, and fieldwork [102,280].…”
Section: Value For Moneymentioning
confidence: 99%